Analisis Vegetasi Model Hutan Kota: Studi Kasus KHDTK Cikampek di Purwakarta, Jawa Barat (Vegetation Analysis of Urban Forest Model: A Case Study of KHDTK Cikampek in Purwakarta, West Java) - Mira Yulianti; Ahmad Gadang Pamungkas; Mamay Maisaroh; Serlina Hestiani Oktian; Nurul Silva Lestari; Donny Wicaksono; Lutfy Abdulah; Muhammad Abdul Qirom; Rachman Effendi (Jurnal Penelitian Hutan Tanaman, 2022)
ABSTRACTThe pressure on the existence of stands in urban areas is very high, while the nature of Special Purpose Forest Areas (KHDTK) is open and easily accessible. As a result, the existence of stands is easily threatened. The purpose of the study was to determine the potential of KHDTK to be used as a reference for tree species selection to support urban forest development. The data was collected using the inventory method. The number of sample plots is 32 plots, which were determined using purposive sampling. The plot size is 20 x 20m, with subplots of 10 m x 10 m, 5 m x 5 m, and 2 m x 2 m. Analysis of the data includes the importance value index, diversity index, richness index, evenness index, anddominance index. The results showed that four species grew well and were able to naturally regenerate in urban forests, such as H. courbaril, P. mooniana, S. mahagoni, and T. verrucosum. The index of diversity, dominance, richness, and evenness of species is classified as moderate. Tree species with natural regeneration capacity that were found in KHDTK Cikampek have the potential to be used in the development of urban forests but need to consider their agro climatic suitability.Keywords: Urban Forest, diversity index, tree species ABSTRAKTekanan keberadaan tegakan di wilayah perkotaan sangat tinggi, sementara sifat Kawasan Hutan Dengan Tujuan Khusus (KHDTK) terbuka dan mudah diakses. Hal ini mengakibatkan tegakan KHDTK mudah terancam. Tujuan penelitian adalah mengetahui potensi KHDTK sebagai rujukan jenis pohon untuk mendukung pembangunan hutan kota. Pengumpulan data dilakukan dengan menggunakan metode inventarisasi. Jumlah plot contoh yang dibangunsebanyak 32 plot dengan penentuan lokasi secara purposive sampling. Setiap unit plot contoh berukuran 20 x 20 m, dengan subplot 10 m x 10 m, 5 m x 5 m, dan 2 m x 2 m. Analisis data tegakan meliputi indeks nilai penting, indeks keragaman jenis, indeks kekayaan jenis, indeks kemerataan jenis, dan indeks dominansi. Hasil penelitian menunjukkan bahwa terdapat empat jenis yang tumbuh baik dan mampu mengalami permudaan secara alami di hutan kota, yaitu H. courbaril, P. mooniana, S. mahagoni dan T. verrucosum. Indeks keragaman, dominansi, kekayaan dan kemerataan jenis tergolong sedang. Jenis-jenis tumbuhan dengan kemampuan regenerasi alami yang terdapat di KHDTK Cikampek berpotensi untuk digunakan dalam pembangunan hutan kota, namun harus disesuaikan dengan kondisi agroklimatnya.Kata kunci: Hutan kota, indeks keragaman jenis, jenis pohon